Servant Leadership, Knowledge Management, and Gotong Royong Culture as Predictors of Teacher’ OCB: The Mediating Role of Trust and Work Motivation - Syafrudin, Syafrudin; Suharyati, Heny; Suhendra, Suhendra (Business and Applied Management Journal, 2026)
This study examines the influence of servant leadership, gotong royong culture, and knowledge management on teachers' Organizational Citizenship Behavior (OCB), with trust and work motivation as mediating variables. A quantitative survey design was used, and data were collected from teachers and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 4.0). The findings indicate that servant leadership, gotong royong culture, and knowledge management have a positive and significant influence on teachers' OCB. In addition, servant leadership and gotong royong culture significantly increase trust, while gotong royong culture and knowledge management positively influence work motivation. Both trust and work motivation were also found to significantly increase teachers' OCB. Furthermore, a mediation analysis indicated that trust and work motivation partially mediate the relationship between servant leadership, gotong royong culture, knowledge management, and teachers' OCB. These results emphasize the importance of integrating leadership practices, local cultural values, and effective knowledge management to foster teachers' extra-role behaviors in educational institutions. This study contributes to the organizational behavior literature in education by highlighting the role of indigenous cultural values, particularly the culture of gotong royong, in strengthening teachers' organizational citizenship behavior (OCB).